Anaclitic personality dimension in women with Alzheimer's disease: comparison with control groups - Henriques-Calado, J.; Duarte-Silva, M. E.; Sousa Ferreira, A. (Personality and Individual Differences, 2017)
This study sought to determine the evaluation of current and pre-morbid personality traits in Alzheimer's disease, as well as personality changes. Psychodynamic framework and Sidney Blatt's personality developmental perspective, anaclitic vs introjective, are taken as references. The study was conducted with four groups which were assessed using the Depressive Experiences Questionnaire, mainly in the form of individual interview sessions. Current personality measure: Alzheimer's disease Group, consisting of 44 female participants (MAge = 81.36 years); Control Group, consisting of 80 female participants from the population at large (MAge = 75.84 years). Pre-morbid personality measure: Alzheimer's disease Group Informants (n = 40); Control Group Informants (n = 42). Results are in line with the psychodynamic literature review and provide new research data. Findings suggest that there is stability across the life cycle in a relatedness/anaclitic/dependency personality style in dementia. Implications of the findings for future research are discussed.